2021
DOI: 10.5817/cp2021-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in videoed accounts of victim blaming for revenge porn for self-taken and stealth-taken sexually explicit images and videos

Abstract: Using video recounts from revenge porn victims, this study explores whether levels of victim blaming differs for the sharing of self- and stealth-taken sexually explicit images and videos. Building on previous work which has demonstrated victim blame for both self- and stealth generated images in occurrences of revenge porn (Zvi & Schechory-Bitton, 2020), the reported study presents an original and ecologically valid methodological approach whereby 342 (76 male, 266 female) participants (Mage = 39.27, SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Additionally, the attitudinal questions indicate a trend towards men diminishing the harms or "badness" of deepfake pornography behaviors. This is consistent with previous findings on deepfake pornography [29], and with other findings around image-based sexual abuse more broadly [7,10].…”
Section: Gender and Ai-ibsasupporting
confidence: 93%
“…Additionally, the attitudinal questions indicate a trend towards men diminishing the harms or "badness" of deepfake pornography behaviors. This is consistent with previous findings on deepfake pornography [29], and with other findings around image-based sexual abuse more broadly [7,10].…”
Section: Gender and Ai-ibsasupporting
confidence: 93%
“…[ 25 ] Men seem to be more accepting of the gender role stereotypes and hence make such attributions. In contrast, a study using videotaped accounts found that men assigned significantly more blame regardless of the victim’s sex,[ 27 ] while another study using pre-service teachers found that neither the victim’s nor the attributor’s gender had an impact on the way blame was assigned. [ 24 ] In a study with predominant female respondents, blame attributions were found less for female victims who have longer relationship with the perpetrator.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth noting that the gender of the victim and the mode of sharing sexually explicit material, whether through video or images, did not seem to have an impact on the level of victim blaming. [ 27 ] Also, individuals with higher age, lower levels of empathy, and higher levels of rape myths acceptance tend to attribute higher levels of victim blaming. [ 24 ] Likewise, individuals lacking prior experience in sexting were more inclined than those with sexting experience to view the situation as grave and to ascribe blame to the victim.…”
Section: Resultsmentioning
confidence: 99%
“…4 Layout of the medium-fidelity interface framework 1 , the interface prototypes were served as static sites with a Jamstack-like architecture. 2 To maximise the participant privacy, data were collected only on the interface prototypes using JavaScript embedded in the web source and an API running on an institutional web server. Scores were saved only after the completion of the experiment.…”
Section: Medium-fidelity Prototypementioning
confidence: 99%
“…Further research on gender and other intersectional aspects (e.g., race, ability) are paramount since women and girls are often the victims of non-consensual pornography [75]. As demonstrated by [2] women suffer higher victims blame and minority groups, especially sexual minorities, are most often the target of cyberbullying [46].…”
Section: Limitations and Future Researchmentioning
confidence: 99%